'Secret shopper' study of residential programs. Issue 4 (21st March 2021) - Knopf, Alison
Abstract : Many parents want their children — even their adult children — with substance use disorders (SUDs) to be in residential treatment. They feel that it's safe. They don't want them to have outpatient buprenorphine or methadone, despite the fact that these medications are first‐line treatment for opioid use disorders (OUD). In addition, many of these children do not have opioid problems — increasingly, stimulants are a problem, and alcohol and marijuana always have been; OUD medications don't work for these SUDs.